1986
DOI: 10.1042/bj2370327
|View full text |Cite
|
Sign up to set email alerts
|

The decrease in phosphatidylinositol 4,5-bisphosphate in ADP-stimulated washed rabbit platelets is not primarily due to phospholipase C activation

Abstract: Addition of 10 micron-ADP to washed rabbit platelets caused platelet shape change and aggregation without release of the contents of the amine-storage granules, and caused a transient decrease (8.8% at 10 s) in the amount of phosphatidylinositol 4,5-bisphosphate (PIP2). By 20 s the decrease in PIP2 was no longer apparent, but by 60 s the amount of PIP2 was again decreased. Addition of thrombin (1 unit/ml), which causes platelet shape change, aggregation and the release of the contents of the amine-storage gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 39 publications
6
21
0
Order By: Relevance
“…Our present data show that stimulation of platelets with thrombin induces a considerable increase in the specific radioactivity of the diester phosphate of all the phosphoinositides. While this increase may appear insignificant compared to the absolute radioactivity in the monoester phosphates, it may explain the 6%0 increase in specific activity of PIP2 reported by Vickers et al [10]. The presented data are supported by Dangelmaier et al [17] who found that IP3 produced upon thrombin stimulation had similar specific 32p-radioactivity as compared to that of PIP2.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our present data show that stimulation of platelets with thrombin induces a considerable increase in the specific radioactivity of the diester phosphate of all the phosphoinositides. While this increase may appear insignificant compared to the absolute radioactivity in the monoester phosphates, it may explain the 6%0 increase in specific activity of PIP2 reported by Vickers et al [10]. The presented data are supported by Dangelmaier et al [17] who found that IP3 produced upon thrombin stimulation had similar specific 32p-radioactivity as compared to that of PIP2.…”
Section: Discussionsupporting
confidence: 79%
“…In platelets the existence of distinct metabolic Abbreviations: PI, phosphatidylinositol; PIP, phosphatidylinositol 4-phosphate; PIP2, phosphatidylinositol 4,5-bisphosphate; PA, phosphatidic acid; GroPI, diacylated phosphatidylinositol pools of PA, PI and PIP2 has been suggested [6][7][8]. Recently, Vickers and Mustard studied the specific [32p]Pi and [3Hlglycerol labelling of the phosphoinositides in both resting and stimulated platelets and proposed separate pools of polyphosphoinositides [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Aggregation in response to either thrombin or ADP caused the incorporation of label into the cytoskeleton, indicating that it is a consequence of aggregation, rather than being dependent on the induction of the release reaction since ADP causes very little release of the contents of the granules of rabbit or human platelets in the Ca2"-containing medium in which the platelets were suspended (22). In addition, reactions involving the formation of thromboxane A2 and inositol trisphosphate are not essential for the incorporation of label into the cytoskeleton since they do not occur during ADP-induced aggregation of rabbit platelets (24). The association of [3H]palmitic acid with the cytoskeleton was dependent on the requirements for aggregation, namely, the presence of an inducer, stirring, Ca2", and, for ADP-induced aggregation of human platelets, fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was initially based on the experimental system used by Burn and his colleagues (21) who used human platelets prelabeled with [3H]palmitic acid. Experiments were designed to compare the effect on the formation of lipid-cytoskeleton complexes of a strong agonist (thrombin) that causes aggregation, the release of granule contents, thromboxane A2 formation (22) and the degradation of phosphatidylinositol 4,5-bisphosphate to inositol trisphosphate and 1,2-diacylglycerol (23), with a weak agonist (ADP) that causes aggregation without appreciable release of granule contents, formation of thromboxane A2 or formation of inositol trisphosphate by rabbit platelets (24), and probably little formation of diacylglycerol. Another reason for comparing the effects of ADP and thrombin was that the association between myosin and F-actin that occurs when platelets are stimulated with thrombin has been found by some investigators ( 12), but not by others (1 1), to also occur when the platelets are stimulated with ADP.…”
Section: Introductionmentioning
confidence: 99%
“…This apparent discrepancy is not surprising, taking into account that PI-PLC does not appear to play a major role in the ADP-induced platelet activation. [42][43][44][45] Oxidative modification of lipoproteins, which may occur in vivo or during isolation, is thought to change their physicochemical and biological properties. If the inhibitory activity of HDL 3 is a consequence of oxidation, one would expect in vitro-oxidized HDL 3 to act on platelet activation more potently than native HDL 3 .…”
Section: Discussionmentioning
confidence: 99%